A temperature-tolerant CRISPR base editor mediates highly efficient and precise gene editing in Drosophila - Doll, Roman M.; Boutros, Michael; Port, Fillip (Science advances, 2023)
CRISPR nucleases generate a broad spectrum of mutations that includes undesired editing outcomes. Here, we develop optimized C-to-T base editing systems for the generation of precise loss- or gain-of-function alleles in Drosophila and identify temperature as a crucial parameter for efficiency. We find that a variant of the widely used APOBEC1 deaminase has attenuated activity at 18° to 29°C and shows considerable dose-dependent toxicity. In contrast, the temperature-tolerant evoCDA1 domain mediates editing of typically more than 90% of alleles and is substantially better tolerated. Furthermore, formation of undesired mutations is exceptionally rare in Drosophila compared to other species. The predictable editing outcome, high efficiency, and product purity enables near homogeneous induction of STOP codons or alleles encoding protein variants in vivo. Last, we demonstrate how optimized expression enables conditional base editing in marked cell populations. This work substantially facilitates creation of precise alleles in Drosophila and provides key design parameters for developing efficient base editing systems in other ectothermic species.
Gesehen am 27.10.2023